Pengaruh Faktor Internal terhadap Return Saham Perusahaan Farmasi di Indonesia Tahun 2020-2024 - Oktafiana Akmal; Yuni Shara (Journal of Trends Economics and Accounting Research, 2025)
Stock return is an important indicator that reflects the level of profit earned by investors. However, fluctuations in stock returns are often influenced by several internal company factors that are not fully understood comprehensively. This study aims to examine the effect of profitability, liquidity, company size, board size, and net income on stock returns in pharmaceutical companies in Indonesia during the period 2020-2024. To solve these problems, a quantitative approach is used with multiple linear regression methods. The data analyzed comes from the financial statements and stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange, with a total sample of 11 companies with a 5-year observation period. This study used multiple linear regression analysis using IBM SPSS 27. The results showed that at a significant level of 95%, it could not be concluded that liquidity, profitability, net worth, and board size had a partial effect on stock returns. However, at the same level of significance, it can be concluded that company size has a partial effect on stock returns. Simultaneously, at the 95% significance level, liquidity, profitability, net worth, firm size, and board size have an effect on stock returns. Profitability, liquidity, company size, board size, and board of directors size have an effect on stock returns. Profitability, liquidity, company size, board size, and net income simultaneously have an Adjusted R Square of 27.2%, which highlights the fact that there are other variables not included in this study that have an influence on stock returns. This research provides insight to investors and company management that company size is an important factor in making investment decisions.